Structural and Macroeconomic Determinants of the Output Decline in Poland : 1990-91 - Ostry, Jonathan (IMF Working Papers; Working Paper ;, 1992)
This paper addresses two questions relating to the output decline in Poland since the initiation of market-oriented reforms at the beginning of 1990. First, to what extent is the decline in output a generalized phenomenon, rather than reflecting the short-term effects of resource reallocation in response to the new relative price structure? Second, what have been the main macroeconomic determinants of the output decline? In response to the first question, the paper finds relatively little evidence to favor a 'structural change' view of the output decline. As far as the second question is concerned, the paper finds that both supply-side and demand-side factors have played a role, depending on the specific time period being considered.